The Implementation of The Si Apik Application for MSMEs in Sidodadi Village, Tempurejo, Jember to Order Financial Reporting: Penerapan Aplikasi Si Apik Pada UMKM Desa Sidodadi Tempurejo Jember Untuk Penertiban Laporan Keuangan - Dafillah Vike Eryana (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
The presence of MSMEs is one of the supports for the community's economy because it contributes to economic growth at the national and regional levels, as a step to realize an economically independent Indonesia. On the other hand, the low capacity of human resources and the lack of mastery of science and technology, make MSME actors unable to produce proper reporting records using applicable standards. This activity aims to provide knowledge that can be applied by MSME actors in Sidodadi Tempurejo Jember Village, so that human resources will continue to develop and understand the development of the times. The method used in this activity is training and mentoring for the Si Apik application. The Si Apik application is a financial information recording application system provided by the Government. There are 10 MSMEs participating in this activity. Training and mentoring for the SI Apik application for MSME actors in Sidodadi Village can improve understanding and knowledge in making financial reports.